The Islamic Political System: A Solution to the Modern Political Issues in the light of Tafsīr Sirāṭ-al-Jinān - Hameed, Dr. Abdul; Ali Nadeem, Mian Saadat (Al-Amīr Research Journal for Islamic Studies, 2023)
As Islam gives a complete code of life, and it has a permanent political system. Rather to this, just as it has given rules and regulations in other spheres of life. It has also given unchangeable laws regarding politics. But Islam did not present a detailed structure of the government but left it to the Islamic Jurists to elaborate the principles regarding the Islamic political system. No corner of life is outside the limits of Islamic teachings. The Prophet (ﷺ) has provided guidance for every aspect of life through his words and deeds which should be kept in our mind is the guarantee of success and prosperity of religion and the world. In this article we will brief the Islamic political system and solution of modern political issues through the interpretation of the Qur’ānic verses in the light of Tafsīr Sirāṭ-al-Jinān by Muftī Muḥammad Qāsim Qādrī. Keywords: Islamic Political System Modern Political Issues, Tafsīr Ṣirāt-al-Jinān, Muftī Muḥammad Qāsim Qādrī, Shari’ah